Hijacker of the Antitumor Immune Response: Autophagy Is Showing Its Worst Facet - Viry, Elodie; Noman, Muhammad Zaeem; Arakelian, Tsolère; Lequeux, Audrey; Chouaib, Salem; Berchem, Guy; Moussay, Etienne; Paggetti, Jérôme; Janji, Bassam (Frontiers in Oncology, 2016)
Macroautophagy (hereafter referred to as autophagy) is a housekeeping process constitutively executed at basal level in all cells to promote cellular homeostasis by regulating organelle and protein turnover. However, autophagy deregulation caused by several stress factors, such as hypoxia, is prevalent in many cancers. It is now well established that autophagy can act as tumor suppressor or tumor promoter depending on tumor type, stage and genetic context. In developed tumors, autophagy promotes the survival of cancer cells and therefore operates as a cell resistance mechanism. Emerging evidence point to the prominent role of autophagy in disabling the anti-tumor immune response by multiple overlapping mechanisms leading to tumor escape from immune cell attack mediated by both natural killer cells and cytotoxic T-lymphocytes. Such a role has inspired significant interest in applying anti-autophagy therapies as an entirely new approach to overcome tumor escape from immune surveillance which constitutes so far a major challenge in developing more effective cancer immunotherapies. In this review, we will summarize recent reports describing how tumor cells, by activating autophagy, manage to hijack the immune system. In particular, we will focus on the emerging role of hypoxia-induced autophagy in shaping the anti-tumor immune response and in allowing tumor cells to outmaneuver an effective immune response and escape immunosurveillance. In keeping with this, we strongly believe that autophagy represents an attractive future therapeutic target to develop innovative and effective cancer immunotherapeutic approaches.